2009
DOI: 10.1039/b812114a
|View full text |Cite
|
Sign up to set email alerts
|

Sculpting the β-peptide foldamer H12 helix via a designed side-chain shape

Abstract: The long-range side-chain repulsion between the (1R,2R,3R,5R)-2-amino-6,6-dimethyl-bicyclo[3.1.1]-heptane-3-carboxylic acid (trans-ABHC) residues stabilize the H12 helix in b-peptide oligomers.Synthetic oligomers with distinct conformational preferences (foldamers) are highly intriguing compounds at the interface of covalent and supramolecular (noncovalent) chemistry. 1 Among foldamers based on remote intrastrand interactions, peptides containing b-amino acid residues are probably the most thoroughly studied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…The oligomers of trans ‐cyclic β‐amino acids may promote C 10 ‐, C 12 ‐, or C 14 ‐helical structures . In addition, four‐membered cis ‐oxetane‐based and trans ‐cyclobutane‐based β‐residues promote 10‐ and 12‐helices, respectively . The NMR‐spectroscopic studies of oligo‐β‐peptides with alternating acyclic monosubstituted β 2 ‐ and β 3 ‐amino acids established the mixed helices with C 10 /C 12 hydrogen bonds .…”
Section: Figurementioning
confidence: 98%
“…The oligomers of trans ‐cyclic β‐amino acids may promote C 10 ‐, C 12 ‐, or C 14 ‐helical structures . In addition, four‐membered cis ‐oxetane‐based and trans ‐cyclobutane‐based β‐residues promote 10‐ and 12‐helices, respectively . The NMR‐spectroscopic studies of oligo‐β‐peptides with alternating acyclic monosubstituted β 2 ‐ and β 3 ‐amino acids established the mixed helices with C 10 /C 12 hydrogen bonds .…”
Section: Figurementioning
confidence: 98%
“…Also, they were used successfully as chiral auxiliaries in the enantioselective reactions of Et 2 Zn with aromatic aldehydes [10,12,8,9]. Apopinane-based ␤-amino acids were used as building blocks in the construction of stable H12 foldameric helices and in Ugi four-centre three-component reactions [11,13,14]. The latter new family of monoterpene-based chiral ␤-lactams and ␤-amino acid derivatives derived from (−)-and (+)-apopinene recently were reported to eliminate the disadvantageous steric effect of the methyl substituent on the pinane ring system [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Fülöp and co-workers recently demonstrated that oligomers of a monoterpene-derived trans-β-AA, notionally a sterically challenged ACHC analog, preferred to adopt a 12-helix conformation in order to avoid long-range side-chain repulsions. 7 In an effort to expand the set of available ring-substituted cyclic β-AAs, we envisaged the preparation of trans-3,3-dimethyl-2-aminocyclobutane-1-carboxylic acid 1 (Figure 1). This compound is a sterically-congested derivative of ACBC, but can also be viewed as a conformationally constrained analog of the β 2 -AA 2-aminomethyl-4-methylpentanoic acid 2, or of the β 3 -AA β-homovaline 3, both of which have been incorporated into designed β-peptide sequences.…”
Section: Introductionmentioning
confidence: 99%